Pelaksanaan Tata Kelola Pemukiman Bagi Kelestarian Lingkungan Atas Pendirian Ekowisata Di Kota Batu - Syahna Hanani Azka; Rini Fidiyani (Universitas Cokroaminoto Yogyakarta, 2025)
The development of tourism in Batu City has experienced a significant increase, contributing 50% to the Regional Gross Domestic Product (PRDB). However, the construction of illegal settlements in the Bumiaji Ecotourism area threatens environmental sustainability. Land conversion and weak environmental enforcement have led to negative environmental impacts. This study aims to examine the governance of settlements and the legal and non-legal impacts of land utilization management in the Bumiaji Ecotourism area. The research methodology used is normative-empirical, with a legislative approach, case approach, and theoretical approach (design with nature and imageability). The study found violations of the Batu City spatial planning, particularly in the Bumiaji Ecotourism area, and its environmental impacts, highlighting the need for an integrative solution based on spatial data and ecological approaches. Moreover, non-legal impacts show environmental degradation caused by improper land use.